The Role of Technology in Enhancing the Quality of Learning in Higher Education - Dr. Muhammad Shahzad Ashfaq (Indus Journal of Social Sciences, 2025)
This study explores the impact of technology on the quality of learning in higher education, with a focus on B.Ed students at Fatima Jinnah Women University, Rawalpindi. In an era of digital transformation, integrating technology into educational practices has become essential for improving student engagement, learning outcomes, and instructional effectiveness. The main objectives of the study were to examine student’s perceptions of technology use in learning, identify the technological tools most frequently used, and assess their influence on academic performance and learning satisfaction. The target population comprised all B.Ed students enrolled at the university. A sample of 120 students was selected using stratified random sampling to ensure representation across academic years. A structured questionnaire was used as the primary instrument, designed to capture both qualitative and quantitative data. The study employed a mixed-methods approach, combining descriptive statistics with thematic analysis. Data were collected through on-site surveys and analyzed using SPSS for quantitative responses and manual coding for open-ended items. The findings revealed that students viewed technology as a significant enhancer of learning quality, particularly in terms of access to resources, interactive learning, and self-paced study. The study recommends integrating advanced digital tools, continuous teacher training, and curriculum updates to fully harness the benefits of educational technology.